Improved absorption and in vivo kinetic characteristics of nanoemulsions containing evodiamine–phospholipid nanocomplex - Hu, Jiangbo (Dove Medical Press, 2014)
PURPOSE: The purpose of this study was to assess the improved absorption and in vivo kinetic characteristics of a novel water-in-oil nanoemulsion containing evodiamine–phospholipid nanocomplex (NEEPN) when administered orally. METHODS: NEEPN was fabricated by loading an evodiamine–phospholipid nanocomplex into a water-in-oil nanoemulsive system. The gastrointestinal absorption of NEEPN was investigated using an in situ perfusion method. The modified in vivo kinetic characteristics of evodiamine (EDA) in NEEPN were also evaluated. RESULTS: Compared with EDA or conventional nanoemulsions containing EDA instead of evodiamine–phospholipid complex, NEEPN with its favorable in vivo kinetic characteristics clearly enhanced the gastrointestinal absorption and oral bioavailability of EDA; for example, the relative bioavailability of NEEPN to free EDA was calculated to be 630.35%, and the effective permeability of NEEPN in the colon was 8.64-fold that of EDA. CONCLUSION: NEEPN markedly improved the oral bioavailability of EDA, which was probably due to its increased gastrointestinal absorption. NEEPN also increased efficacy and reduced adverse effects for oral delivery of EDA. Such finding demonstrates great clinical significance as an ideal drug delivery system demands high efficacy and no adverse effects.